Effect of Semicarbazones on Endogenous Protein Hydrolysis in Liver Homogenate - Raghav, N.; Kaur, Ravinder; Singh, Mamta (Asian Journal of Chemistry, 2010)
Semicarbazones of substituted benzaldehydes were synthesized and their effect on endogenous protein hydrolysis in liver homogenate was studied. It was found that p-nitrobenzaldehyde semicarbazone exerted maximum effect.